Aerophilic debubbling - Bert J. C. Vandereydt; Saurabh Nath; Kripa K. Varanasi (Proceedings of the National Academy of Sciences, 2026)
Gas bubbles frequently accumulate at liquid interfaces, compromising throughput, selectivity, and stability across scales from microfluidics to natural ecosystems. Here, we experimentally show that highly permeable aerophilic membranes placed on a liquid–air interface annihilate bubbles within milliseconds. This ultrafast regime appears only above a critical permeability threshold, where the flow departs from classical Darcy-driven dynamics in micropores. We quantitatively characterize this aerophilicity-mediated debubbling process by examining local interactions at the scale of single bubbles approaching the membrane and identify three asymptotic evacuation regimes, the physics of which we capture through simple scaling laws.